THE EFFECT OF APPLYING COOPERATIVE LEARNING MODEL ON BIOLOGY COMPETENCE: LITERATURE STUDY ABOUT NUMBERED HEAD TOGETHER - Wilny Chintya; Azwir Anhar; Ganda Hijrah Selaras; Lufri Lufri (Universitas Negeri Padang, 2021)
The Numbered Head Together (NHT) learning model is one type of cooperative learning model designed to influence the interaction patterns of students. The Numbered Head Together (NHT) cooperative learning model can encourage students to increase cooperation in learning both cooperation between students and between teachers and students will be able to increase tolerance and self-confidence. The purpose of this study was to obtain a description of the effect of using the Numbered Head Together (NHT) learning model on the biology learning competence of students This type of research is ex post facto research. The data used is secondary data, namely data sourced from scientific journal articles accredited by Sinta which were selected as samples the data collection technique in this study was carried out by taking selected journal articles as samples and related to the effect of implementing the Numbered Head Together (NHT) learning model. The data analysis technique uses the steps, namely, data reduction, data presentation, and drawing conclusions and verification the results showed that there was an increase in the learning competence of students using the Numbered Head Together (NHT) learning model. The NHT learning model makes students readiness in learning because they have discussed the material to be studied in advance. Students become more active and dominate during the learning process so that the teacher only acts as a facilitator and motivator.